Utilização de resíduos da filetagem de tilápia-do-nilo(Oreochromis niloticus) na obtenção de concentrado protéico de peixe:caracterização físico-química e aceitação sensorial - Vidal, Juliana Maria Aderaldo (2007)
This study aimed to use mechanically separated mince (MSM) from the residues left after filleting Nile tilapia (Oreochromis niloticus Linnaeus, 1757) to obtain a protein concentrate for human consumption and to assess its proximal composition and sensory characteristics. Three laboratory scale methods of obtaining fish protein concentrate (FPC) from MSM were studied. FPC evaluation included process yield, protein, fat and moisture contents as well as water activity. Based on these preliminary results a test procedure was established to obtain FPC. Yield, proximal composition, water activity sensory evaluation and microbial counts were analyzed on the dry FPC. Sensory evaluation used affective tests and hedonic scales relative to the ideal value for appearance, color and aroma of the product and was accomplished by 48 untrained tasters Five levels of FPC (0%, 15%, 22.5%, 30% and 37.5%, according to the recommended daily intake (RDI) of protein for young adults) were then included in a food formulation based on rice. These samples were identified, respectively, as: A, B, C, D and E were evaluated for appearance, color, aroma, taste and global acceptance by 80 untrained tasters using structured hedonic scales of nine points, following a balanced complete block design. The intention of consumption by the tasters was also assessed using a nine point scale. Data from chemical composition of MSM and FPC were submitted to descriptive analysis. Sensory data were analyzed by graphic design, descriptive analysis, analysis of variance (ANOVA) and Tukey test, using the SPSS statistical program v.13.0 FPC has a yield of 18.34%, and contained 1.38% moisture, 62.39% protein, 32.63% fat, 2.26% ash and had 0.16 Aw. The increase in protein percentage in FPC related to MSM was approximately four times. Microbial counts indicated that the experimental FPC is safe according to Brazilian microbiological standards and therefore it is fit for human consumption. Sensory evaluation of dry FPC powder expressed as acceptance by tasters frequency was 60.4% for color, 51.1% for general appearance and 41.7% for aroma. Description of flavor with terms like "typical of fish" was reported by only 44.2% of the tasters, suggesting the need for a more efficient deodorizing process and showing a balance in relation to the group of tasters that did not notice the characteristic smell. With regard to the perceived intensity of odor, 68.8% of the tasters considered the product ideal, which suggests an odor highly acceptable. Sensory evaluation of CPP included in the rice base showed the sample with 0% of CPP significantly (p 0.01) different from all other samples added of CPP for all attributes studied. Sample B (15% added FCP) however showed the best acceptability among the samples containing FPC. Thus, FPC obtained from MSM from Nile tilapia is a raw material acceptable to use as a food ingredient in various food bases as showed in this study with rice which is considered a neutral food base. Moreover, it is possible to add value to a residual food material offering an alternative source of protein at a relatively low cost.